Joint affine and deformable three‐dimensional networks for brain MRI registration. Issue 3 (22nd January 2021) - Zhu, Zhenyu; Cao, Yiqin; Qin, Chenchen; Rao, Yi; Lin, Di; Dou, Qi; Ni, Dong; Wang, Yi
Abstract : Purpose: Volumetric medical image registration has important clinical significance. Traditional registration methods may be time‐consuming when processing large volumetric data due to their iterative optimizations. In contrast, existing deep learning‐based networks can obtain the registration quickly. However, most of them require independent rigid alignment before deformable registration; these two steps are often performed separately and cannot be end‐to‐end. Methods: We propose an end‐to‐end joint affine and deformable network for three‐dimensional (3D) medical image registration. The proposed network combines two deformation methods; the first one is for obtaining affine alignment and the second one is a deformable subnetwork for achieving the nonrigid registration. The parameters of the two subnetworks are shared. The global and local similarity measures are used as loss functions for the two subnetworks, respectively. Moreover, an anatomical similarity loss is devised to weakly supervise the training of the whole registration network. Finally, the trained network can perform deformable registration in one forward pass. Results: The efficacy of our network was extensively evaluated on three public brain MRI datasets including Mindboggle101, LPBA40, and IXI. Experimental results demonstrate our network consistently outperformed several state‐of‐the‐art methods with respect to the metrics of Dice index (DSC), Hausdorff distance (HD), and average symmetric surface distance (ASSD). Conclusions: The proposed network provides accurate and robust volumetric registration without any pre‐alignment requirement, which facilitates the end‐to‐end deformable registration.